Skolans svenskämne i 1900-talets språk- och litteraturvetenskapliga forskning - Holmberg, Per; Martinsson, Bengt-Göran (Nordic Journal of Educational History, 2026)
The school subject Swedish in twentieth century linguistic and literary research. This article explores the largely overlooked research on L1 education in Sweden conducted before L1 research became an established field in the early 2000s. It examines how Sweden’s educational reforms of the 1960s and 1970s and shifts in academia shaped the development of L1 research. A review of 28 doctoral theses from 1955 to 1998, primarily within Scandinavian Languages and Literature, reveals distinct divergences in research questions, materials, methods, and theoretical frameworks compared to the disciplinary mainstream. These differences are linked to specific academic environments and supervisors. Drawing on Abbott’s fractal theory and Bernstein’s concepts of singularities and regions, the study highlights how a field’s evolution is dependent on both external and internal factors.